Institutions and the turn-of-the-year effect: Evidence from actual institutional trades - Lynch, Andrew; Puckett, Andy; Yan, Xuemin (Sterling) (Journal of Banking & Finance, 2014)
Using a large proprietary database of institutional trades, we investigate whether institutional investors drive the turn-of-the-year (TOY) effect. Institutions that engage in window dressing, tax-loss selling, or risk shifting will contribute to the TOY effect by selling small, poorly performing stocks at the end of December and/or buying those same stocks at the beginning of January. We find abnormal pension fund selling in small stocks with poor past performance during the final trading days in December, providing some support for the window dressing hypothesis. However, we find little evidence that institutional tax-loss selling or risk-shifting trading strategies contribute to TOY returns. Furthermore, stocks with no institutional trading around the year-end exhibit considerably stronger TOY return patterns than stocks in which institutions trade. Taken together, our results suggest that institutions play a limited role in driving the TOY effect.